2021
DOI: 10.5606/tftrd.2021.6273
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of balance, fall risk, and related factors in patients with fibromyalgia syndrome

Abstract: Objectives: In this study, we aimed to evaluate whether fibromyalgia patients had a higher fall risk compared to healthy individuals and to identify its relationship, if there was an increase, with clinical features. Patients and methods: Between March 2018 and September 2018, a total of 50 consecutive female patients with fibromyalgia (median age: 35 years; interquantile range [IQR], 27 to 40 years) and 50 healthy female volunteers (median age: 30 years; IQR, 23 to 40 years) were included in the study. Pain w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
2
5
0
2
Order By: Relevance
“…Previous studies have examined and documented balance impairments in FMS individuals and the effects of different exercise regimens that aim to improve postural stability [40,41]. Impaired postural control and risk of falling were identified in FMS individuals compared to controls, and the risk of falling was increased in individuals without taking medication [22]. Similar to our study results, Gucmen et al [24] demonstrated a strong relationship between cervical repositioning tests and static and dynamic balance.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous studies have examined and documented balance impairments in FMS individuals and the effects of different exercise regimens that aim to improve postural stability [40,41]. Impaired postural control and risk of falling were identified in FMS individuals compared to controls, and the risk of falling was increased in individuals without taking medication [22]. Similar to our study results, Gucmen et al [24] demonstrated a strong relationship between cervical repositioning tests and static and dynamic balance.…”
Section: Discussionsupporting
confidence: 86%
“…In a survey of 2596 FMS patients, postural control impairments were identified as among the most prevalent symptoms (45%) [21]. It is anticipated that clinical symptoms such as pain, sleep disturbances, physical fatigue, decreased muscle strength and endurance, impaired proprioception, anxiety, sensory deficits, and cognitive impairments may contribute to postural instability [21,22]. Chronic pain and fatigue are the primary symptoms of FMS [23].…”
Section: Introductionmentioning
confidence: 99%
“…The gains in neuromuscular variables from 2023 402 (11 ) this online protocol are promising for counteracting the effects of strength loss when compared to previous studies with on-site intervention (27,28). Balance changes are directly related to the risk of falling, where women with fibromyalgia have a 45% higher chance of falls when compared to healthy women (29). Decreases found in the balance variables in this pilot study reinforce a better performance in postural control, being in accordance with other studies (30,31).…”
Section: Specific Initial Resultssupporting
confidence: 85%
“…Balance disorders and the effect of various exercise programs on this condition in FMS patients have been researched in earlier studies [33][34][35]. Balance disorder and increased risk of falling were also detected in drug-free FMS patients [36]. Poor balance status in FMS has been attributed to various factors, including decreased muscle strength and performance, cognitive dysfunction, impairment in the sensory or motor system, and the existence of trigger points [35].…”
Section: Discussionmentioning
confidence: 99%